Maintaining project alignment : a grounded theory study of project managers in the Public Works Department of Malaysia (PWDM) - Mohamad Zainal, Hannerita (Curtin University, 2012)
The main aim of this thesis is to examine and provide theoretical understandings of the reasons why project managers have varying success in delivering projects. To this end, a grounded theory approach is adopted for the collection and analysis of data in the Public Works Department of Malaysia (PWDM). The theoretical perspectives that emerge from the analysis provide new insights into the previously under-researched area of non-Western/developing national contexts.The main finding is that project manager’s endeavor in ‘Maintaining Project Alignment (MPA)’. This refers to how project managers of PWDM attempt to deal with the ongoing challenges of effectively managing a project. During this process the project manager is required to monitor ‘project health’. If indicators of project health show a negative pattern, the project manager must then attempt to maintain ‘Project Alignment’.The theoretical insights produced in the study are presented by employing a coding paradigm or a paradigm model in which the researcher identifies a Central phenomenon (a central category about the phenomenon, i.e. Maintaining Project Alignment (MPA)), explores Causal conditions (categories of conditions that influence the phenomenon, i.e. Critical Success Factors (CSF) — Project Ambivalence, Project Stakeholder, Technical risk, External risk, and National culture), identifies the Context conditions (the broad conditions that influence the strategies, i.e. Organizational structure (OS) — Recruitment, Training initiative, Project autonomy, and Role conflict), the Intervening conditions (the narrow conditions that influence the strategies, i.e.Project Management Competencies (PMC) — Leadership, Problem solving, Reflective practice, Teamwork, and Innovating), specific Strategies (an action that results from the phenomenon, i.e. Managing Change (MC) - Reconciling competing stakeholder goals, Being intermediary, and interfacing), and delineates the consequences (outcomes of the strategies, i.e. Success Criteria Factor (SCF) - Intrinsic goals, Tangible results, and User satisfaction ) of this phenomenon.The literature indicates the existence of many categories for Maintaining Project Alignment (MPA). However there are few, if any, theoretical explanations that connect and contextualize these categories into a single framework. In this study this issue is addressed by referring to three challenges of rethinking project management proposed by (Winter, Smith, Morris, et al. 2006) whereby project management is moved from being an instrumental process to being a social process; from being conceptualised as a life cycle model to being focused on theories of complexities; and from emphasising practitioners as trained technicians to emphasising practitioners as reflective practitioner.In conclusion, the grounded theory of ‘Maintaining Project Alignment (MPA)’ in this study contributes to the understanding of the experience of a project manager in managing a project. The theory of ‘Maintaining Project Alignment (MPA)’ developed in this study has extended the understanding of project management by illuminating the importance of developing a theory that calls attention to and bridges the existing gap between theory and practice.